IBDs and the pediatric age: Their peculiarities and the involvement of the microbiota. Issue 1 (January 2021) - Cococcioni, Lucia; Panelli, Simona; Varotto-Boccazzi, Ilaria; Carlo, Domenico Di; Pistone, Dario; Leccese, Gabriella; Zuccotti, Gian Vincenzo; Comandatore, Francesco
Abstract: Inflammatory Bowel Diseases (IBDs) are gastrointestinal disorders characterized by chronic, relapsing inflammation, with growing incidence worldwide over the last decades and distinctive features in the pediatric age. An increasing body of evidence indicates that gut microbiota plays a major role in inflammatory disorders, including IBDs. In this review we will discuss the most recent evidences on dysbiotic changes associated with gut inflammation, as well as environmental and genetic factors contributing to IBD pathogenesis, with a focus on the peculiarities of the pediatric age.